3D self-assembled polar vs. non-polar NiO nanoparticles nanoengineered from turbostratic Ni3(OH)4(NO3)2 and ordered β-Ni(OH)2 intermediates - Pejova, Biljana; Eid, Arej; Lari, Leonardo; Althumali, Ahmad; Šiller, Lidija; Kerrigan, Adam; Pejov, Ljupcho; Lazarov, Vlado K. (Royal Society of Chemistry, 2024)
A surfactant-free ammonia and carbamide precursor-modulated engineering of self-assembled flowerlike 3D NiO nanostructures based on ordered β-Ni(OH)2 and turbostratic Ni3(OH)4(NO3)2 nanoplate structured intermediates is reported. By employing complementary structural and spectroscopic techniques, fundamental insights into structural and chemical transformations from intermediates to NiO nanoparticles (NPs) are provided. FTIR, Raman and DSC analyses show that the transformation of intermediates to NiO NPs involves subsequent loss of NO3− and OH− species through a double-step phase transformation at 306 and 326 °C corresponding to the loss of free interlayer ions and H2O species, respectively, followed by the loss of chemically bonded OH− and NO3− ions. Transformation to NiO NPs via the ammonia route proceeds as single-phase transition, accompanied with a loss of OH− species at 298 °C. The full transformation to NiO NPs of both intermediates is achieved at 350 °C through annealing in the air atmosphere. Ammonia-derived NPs maintain nanoflower morphology by self-assembling into nanoplates, which is enabled by H2O-mediated adhesion on the NiO NPs’ {100} neutral surfaces. Structural transformations of turbostratic Ni3(OH)4(NO3)2 nanoplates result in the formation of NiO NPs dominantly shaped by inert polar OH-terminated (111) atomic planes, leading to the loss of the initial self assembled 3D structure. DFT calculations support these observations, confirming that H2O adsorbs dissociatively on polar {111} surfaces, while only physisorption is energetically feasible on {100} surfaces. NiO NPs obtained via two different routes have overall different properties: carbamide-derived NPs are 3 times larger (15.5 vs. 5.4 nm), possess a larger band gap (3.6 vs. 3.2 eV) and are more Ni deficient. The intensity ratio of surface optical (SO) modes to transversal and longitudinal optical modes is ∼40 times higher in the NiO NPs obtained from β-Ni(OH)2 compared to Ni3(OH)4(NO3)2-derived NPs. The SO phonon lifetime is an order of magnitude shorter in NiO obtained from β-Ni(OH)2, reflecting a much smaller NP size. The choice of a precursor defines the size, morphology, crystallographic surface orientations and band gap of the NiO NPs, with Ni deficiency providing pathways for utilizing them as p-type materials, allowing for the precise nanoengineering of polar and neutral surface-dominated NiO NPs, which is of exceptional importance for use in catalysis.
Keywords: NiO NPs, nanostructures, flower-like morphology, nanoplates, nanorods, nanocubes, nickel oxide, hydroxide-based NPs, Ni(OH)2, Ni3(OH)4(NO3)2, annealing-induced phase transformation.